Keratin-derived S/N co-doped graphene-like nanobubble and nanosheet hybrids for highly efficient oxygen reduction. Issue 41 (28th September 2016) - Zhang, Jian; Zhou, Huang; Liu, Xiaobo; Zhang, Jie; Peng, Tao; Yang, Jinlong; Huang, Yunhui; Mu, Shichun
Abstract : Novel S/N co-doped graphene-like nanobubble and nanosheet hybridized architectures were prepared. Such graphene-like hybrids exhibit a better ORR performance and fuel tolerance than commercial Pt/C catalyst in alkaline media. Abstract : Heteroatom doped graphene-based materials generally offer great advantages towards constructing advanced catalysts. In this work, we develop a novel sulfur (S) and nitrogen (N) co-doped graphene-like nanobubble and nanosheet hybridized architecture prepared by a cost-efficient strategy using keratin containing abundant N and S sources as the precursor and KOH as the activating agent. After further graphitization and ammonia treatments at 1000 °C, it displays an ultrahigh surface area (1799 m 2 g −1 ) as well as abundant active heteroatom dopants (graphitic-N, pyridinic-N and thiophene-S). Electrochemical measurements show that its onset potential is nearly 26 mV positive than that of the commercial Pt/C catalyst towards the oxygen reduction reaction (ORR) in alkaline media, and it has higher electrochemical stability and fuel tolerance than Pt/C. To the best of our knowledge, such ORR activity is the best one among the metal-free graphene-based catalysts in alkaline media, and much higher than that of the other reported biomass-derived carbon-based catalysts. Significantly, when employed as the air electrode for zinc–air batteries, this graphene-like hybrid catalyst displays an outstanding performance compared to the Pt/C catalyst. Moreover, compared with Pt/C, such a catalyst also exhibits comparable ORR activity and higher stability in acidic media. The outstanding ORR performance can be mainly attributed to its novel hybridized graphene-like architecture, which endows it with a similar thin layered property to graphene and an ultrahigh surface area as well as excellent hierarchical porous structures, and to the synergistic effect of the appropriate graphitization degree and high content of active heteroatoms.